STUDI HUKUM PERBANDINGAN SISTEM KETATANEGARAAN MALAYSIA DAN INDONESIA - Nasaruddin Umar (TAHKIM, 2013)
Generally Malaysian legal system is influenced by the tradition of English Common Law System while the Indonesian legal system more mengadobsi tradition of Dutch civil law system in addition to the system of Islamic law and customary law systems also affect the national law of each country. Comparative study of constitutional law system Malaysia and Indonesia is a constitutional law studies using normative legal research with comparative law approach to examine the advantages and disadvantages of the legal systems of both countries, especially in the state system between the two countries including the judicial system, in order to obtain a overview of the differences and similarities of national legal systems of both countries. Based on the research results through liberary research found that institutional format nagara Malaysia and Indonesia have differences in terms of both form the state and the ruling party. Malaysia is a country that adheres to the type of federal state which includes federal and state government system with a democratic monarchy. While the Indonesian state, which includes the unitary form of the central government and autonomous regions with a republican system of government with the principles of constitutional democracy. In addition, it was also discovered that a power-sharing system of Malaysia and Indonesia when viewed from theory Trias politica have differences. Where The diPertuang Agong as the Head of State Malaysia holds three (3) as well as the power of the executive, the legislative and judiciary powers. While in Indonesia the third power of each stand-alone, in which executive power is held by the President, the legislative power by Parliament and judicial power in the hands of the Supreme Court and the Constitutional Court. Keywords: comparative studies, constitutional law, Malaysia, Indonesia.